Why Government Schools are Merged in Haryana - Sangwan, Sher Singh (JOURNAL OF INDIAN EDUCATION, 2023)
Increasing the outreach of Government Schools (GSs) has always been an agenda of welfare governments, but the issue of their quality was relegated to the background. Hence, Private schools have become the first choice of most parents. To improve teacher-pupil ratio, as many as 12 State governments in India have tried to implement the policy of school ‘Closures and Mergers’ since 2013. Notwithstanding, quality deterioration continued. But State of Delhi since 2014 has adopted different model and its GSs outperformed private schools in 2020–21. Haryana has also preferred the policy of closures and mergers of its adjoining schools with lesser number of students. To comment on this policy, the author has studied the trend in number of schools since 1966 and status of students enrolled by social category in government and private schools at primary, secondary and higher secondary levels. The analysis has thrown up that the number of private schools in Haryana surpassed GSs around the year 2010 –11 except the primary ones. Students’ enrolment is fast decreasing especially at the level of primary Government schools which are 87 per cent in numbers but student enrolment is 45 per cent only. Hence, most of the schools identified for closures are the primary schools. Teachers’ Unions are opposing, but policy does not appear against the interest of students. However, the policy alone will not succeed in improving the quality of education. Government has to improve the monitoring policy and teachers’ training and exposure. Government employees may be motivated to send their children to government schools by giving grace marks for admission to higher institutes and government services.